Highly Active Bifunctional Oxygen Electrocatalytic Sites Realized in Ceria–Functionalized Graphene. (8th May 2020) - Grewal, Simranjit; Macedo Andrade, Angela; Liu, Ziqi; Garrido Torres, Jose Antonio; Nelson, Art J.; Kulkarni, Ambarish; Bajdich, Michal; Lee, Min Hwan
Abstract: The development of efficient, durable, and cost‐effective bifunctional electrocatalysts for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) is essential in the advancement of solar fuels, metal–air batteries, and unitized regenerative fuel cells. This work demonstrates an effective approach of activating 2D carbon for highly efficient bifunctional oxygen reactions without N‐doping, let alone a transition metal–nitrogen (TM–N x ) moiety, the usual component needed for high oxygen electrocatalytic activities. A solvothermally synthesized ceria (CeO2 )–hydroxylated graphene hybrid catalyst shows excellent bifunctional ORR/OER activities both in alkaline and acidic solutions. Density functional theory calculations reveal that the activation of graphene occurs via topmost oxygens on ceria surface, but only when low coverage of hydroxyl groups is present on graphene. Furthermore, catalytically active forms of graphene share similar hydroxylated structural motifs. Finally, a simple approach of dramatically enhancing durability even in acidic media is demonstrated. Abstract : Graphene is stably functionalized with the aid of ceria to render a highly active bifunctional oxygen electrocatalyst in both acidic and alkaline media. A density functional theory calculation identifies the catalytically active sites. A simple approach to stabilize the catalytic activity in acidic media is also demonstrated.